Adaptable system for robotic telerehabilitation with serious games - Consoni, Leonardo José (2017)
Over the last decades, the worldwide increase in cases of neuromotor health issues, due to overall population aging, motivated a growing research interest in improving rehabilitation processes with robotics. The performed studies opened the possibility to include other auxiliary technologies in physical and occupational therapy, like virtual reality and remote interaction between patients and therapists. Although there are verified and potential benefits to rehabilitation provided by these techniques, there are still few attempts towards tooling and methodology standardization, which could lead to faster developments. This work describes the creation of a proposed common computational platform for robotic rehabilitation studies, with support for virtual games and telecommunication. A preceding literature review helped to determine the requirements and development tools for such multipurpose system. Its modular and configurable design aims to allow components reuse and adaptability to different robotic therapy cases, even ones not initially intended, preventing work duplication. Details about the system\'s structure, components and operation are shown, focusing its provided flexibility. Multiplayer games involving position and force control are also created to test the proposed system in real and simulated environment, in order to demonstrate its usability for application and evaluation of robotic rehabilitation strategies. At the end, the results obtained so far are discussed and considerations about missing points and future developments are made.